Exacerbation of Ventilation-Induced Lung Injury and Inflammation in Preterm Lambs by High-Dose Nanoparticles. Issue 1 (December 2017) - Inocencio, Ishmael; Bischof, Robert; Xiang, Sue; Zahra, Valerie; Nguyen, Vy; Lim, Tammy; LaRosa, Domenic; Barbuto, Jade; Tolcos, Mary; Plebanski, Magdalena; Polglase, Graeme; Moss, Timothy
Abstract Mechanical ventilation of preterm neonates causes lung inflammation and injury, with potential life-long consequences. Inert 50-nm polystyrene nanoparticles (PS50G) reduce allergic inflammation in the lungs of adult mice. We aimed to confirm the anti-inflammatory effects of PS50G in a sheep asthma model, and investigate the effects of prophylactic administration of PS50G on ventilation-induced lung injury (VILI) in preterm lambs. We assessed lung inflammatory cell infiltration, with and without PS50G, after airway allergen challenge in ewes sensitised to house dust mite. Preterm lambs (0.83 gestation) were delivered by caesarean section for immediate tissue collection (n = 5) or ventilation either with (n = 6) or without (n = 5) prophylactic intra-tracheal administration of PS50G nanoparticles (3% in 2 ml). Ventilation was continued for a total of 2 h before tissue collection for histological and biomolecular assessment of lung injury and inflammation. In ewes with experimental asthma, PS50G decreased eosinophilic infiltration of the lungs. Ventilated preterm lambs showed molecular and histological signs of lung injury and inflammation, which were exacerbated in lambs that received PSG50G. PS50G treatment decreased established inflammation in the lungs of asthmatic sheep. However, prophylactic administration of PSG50 exacerbated ventilation-induced lung injury and lung inflammation in preterm lambs.